Greater efficacy of a combination of conservative therapies for thumb base OA in individuals with lower radial subluxation – a pre-planned subgroup analysis of the COMBO trial. Issue 11 (November 2021) - Deveza, L.A.; Robbins, S.R.; Duong, V.; Fu, K.; Wajon, A.; Eyles, J.P.; Jongs, R.; Riordan, E.A.; Oo, W.M.; Hunter, D.J.
Summary: Objective: To investigate heterogeneous effects of a combination of conservative therapies compared with an education comparator for thumb base (TB) osteoarthritis (OA) according to clinically relevant characteristics. Methods: Pre-planned subgroup analysis of the COMBO trial ( n = 204) which compared a combination of education on self-management and ergonomic principles, a prefabricated neoprene splint, hand exercises, and diclofenac sodium gel, with education alone for radiographic and symptomatic TB OA. Primary outcomes were change in pain (visual analogue scale [VAS], 0–100 mm) and hand function (Functional Index for Hand Osteoarthritis questionnaire, 0–30) from baseline to week-6. Other outcomes were grip and tip-pinch strength and patient's global assessment (PGA) (VAS, 0–100 mm). Possible treatment effect modifiers were the presence of interphalangeal joint pain, erosive hand OA, radiographic thumb carpometacarpal joint subluxation (higher vs equal or lower than the sample mean), and baseline radiographic OA severity (Kellgren Lawrence grade). Linear regression models were fitted, adding interaction terms for each subgroup of interest. Results: The treatment effects of the combined intervention at 6 weeks were greater in participants with lower joint subluxation compared with those with greater subluxation (pain −11.6 [95%CI −22.2, −9.9] and 2.6 [−5.5, 10.7], respectively, difference between the subluxation groups 14.2 units (95% CI 2.3, 26.1), p -value 0.02; and PGA −14.0 [−22.4, −5.5] and 1.5 [−6.2, 9.3), respectively, difference between the subluxation groups 15.5 units (95% CI 4.2, 26.8), p -value 0.03). There was no statistically significant heterogeneity for the other subgroups. Conclusion: A combination of conservative therapies may provide greater benefits over 6 weeks in individuals with lower joint subluxation, although the clinical relevance is uncertain given the wide confidence intervals. Treatment strategies may need to be customized for those with greater joint subluxation. Trial registration number: ACTRN 12616000353493.